Compound copper powder and its preparation method and application
By combining porous copper powder A with solid copper powder B, a composite powder with controllable pore size and loose ratio is solved, and the problem of cumbersome preparation technology of existing copper powder is achieved, and the capillary and permeability matching of copper heat pipes is achieved. , meet the needs of batch production performance.
Patent Information
- Application Number
- CN202211648826.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The existing copper powder preparation process is cumbersome and cannot meet the needs of copper heat pipes with excellent batch production performance.
The composite method of porous copper powder A and solid copper powder B is used to prepare a composite powder with a specific micromorphology through thermal reduction and oxidation treatment, forming a composite powder with controllable pore size and controllable loose ratio for use in Prepare heat pipes.
The capillary force and permeability of the heat pipe are achieved to achieve excellent matching, meeting the requirements of batch production performance.
Smart Images

Figure CN115740431B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powder materials, and specifically relates to a compound copper powder and a preparation method and application thereof. Background Art
[0002] Porous metal materials have both structural and functional properties due to their special structure. They not only have a large specific surface area, excellent mass transfer performance, strong material adsorption capacity, permeability and shock absorption due to the pore structure, but also have high conductivity, excellent ductility and catalytic activity due to metal properties. They are a new type of functional porous structural material that is developing extremely rapidly and are often used to prepare various metal products such as heat dissipation materials, catalysts, electrode materials, filter plates, and oil-containing bearings. In recent years, with the rapid development of the radiator manufacturing industry, the performance requirements for metal heat pipe products have been continuously improved, and the structure and performance requirements of the porous copper powder raw materials used to prepare metal heat pipe products have also become increasingly higher.
[0003] For example, copper heat pipes are a type of highly efficient phase-change heat transfer element, which is widely used in the technical fields of heat transfer and heat dissipation. Currently, atomized copper powder is mainly used in copper heat pipe materials. The existing technology fills copper powder and copper tubes with vibration and sintering. This composite structure of copper powder and copper tube requires that the copper powder used must be more irregular to ensure that after sintering, the capillary structure pores are more refined and show stronger capillary force. On the other hand, it is also necessary to control the shrinkage rate of the copper powder to ensure that the copper powder and the inner wall of the copper tube have good bonding strength.
[0004] Therefore, how to provide a copper powder whose preparation process is simple and can be suitable for mass production of copper heat pipes with excellent performance is a technical problem that needs to be solved at present. Summary of the invention
[0005] The technical purpose of the present invention is to at least solve the problems that the existing copper powder preparation process is complicated and its performance cannot meet the requirements of mass production of copper heat pipes with excellent performance.
[0006] This purpose is achieved through the following technical solutions:
[0007] In the first aspect, the present invention discloses a composite copper powder, wherein the copper powder is composed of a porous copper powder A and a solid copper powder B, wherein the porous copper powder A is a spherical or quasi-spherical powder, wherein the spherical or quasi-spherical powder contains interconnected cuprous powders, wherein the cuprous powders are dendritic, and each dendritic cuprous powder is cross-stacked to form the porous structure; the pore size of each pore of the porous structure is 0.1 to 5 μm, and the porosity is 10 to 75%; and the bulk ratio of the composite copper powder is 0.8 to 2.8 g / cm 3 .
[0008] In some embodiments of the present invention, the bulk ratio of the porous copper powder A is 0.8 to 2.4 g / cm 3 , preferably 0.8 to 1.0 g / cm 3 ; The particle size of the porous copper powder A is -60 to +200 mesh, wherein 50% ≤ -60 to +150 mesh ≤ 55 to 70%;
[0009] The bulk ratio of the solid copper powder B is 2.2 to 3.8 g / cm 3 , preferably 2.4 to 2.8 g / cm 3 ; The particle size of the solid copper powder B is D50=50~150μm, preferably D50=50~80μm.
[0010] In some embodiments of the present invention, the mass ratio of the porous copper powder A to the solid copper powder B is (1-9):(9-1).
[0011] In some embodiments of the present invention, the porous copper powder A is prepared by subjecting a copper oxide powder raw material to thermal reduction treatment; the copper oxide powder raw material is a copper oxide powder having a porous structure and / or a hollow structure;
[0012] The copper oxide powder with a porous structure is at least one of electroplating grade copper oxide and calcined grade copper oxide; the particle size of the copper oxide powder with a porous structure satisfies: D50=28-40 μm;
[0013] The copper oxide powder having a hollow structure is a powder having a particle size of 1.0 to 100 μm obtained by reduction-oxidation treatment of cuprous oxide.
[0014] In some embodiments of the present invention, the bulk ratio of the copper oxide powder raw material is 0.6 to 1.5 g / cm 3 , preferably 0.8 to 1.2 g / cm 3 When the copper oxide powder raw material is composed of copper oxide powder with a porous structure and copper oxide powder with a hollow structure, the mass ratio of the two is (1-9):(9-1).
[0015] In some embodiments of the present invention, the porous copper powder A is prepared by subjecting a copper oxide powder raw material to thermal reduction treatment, comprising the following steps:
[0016] 1) subjecting a copper oxide powder raw material to a thermal reduction treatment to obtain a reduction pre-treated product;
[0017] 2) Cooling, crushing and sieving the reduction pre-treated product of step 1) to obtain the porous copper powder A.
[0018] In some embodiments of the present invention, the method further comprises subjecting the reduction pre-treated product obtained in step 1) to the following treatment:
[0019] 2.1) the reduction pretreatment product is subjected to oxidation treatment to obtain an oxidation product;
[0020] 2.2) the oxidation product is further subjected to thermal reduction treatment;
[0021] The steps 2.1) and (2.2) are repeated 1 to 6 times, and then cooled, crushed and sieved to obtain the porous copper powder A.
[0022] In some embodiments of the present invention, the thermal reduction treatment in step 1) and step 2.2) is carried out in a reducing atmosphere containing nitrogen, wherein the volume percentage of nitrogen in the reducing atmosphere is 10 to 90%, preferably ammonia decomposition gas;
[0023] The temperature of the thermal reduction treatment is 300-900°C, preferably 400-800°C, and the treatment time is 1-8h;
[0024] The oxidation treatment in step 2.1) is carried out in air, high-purity oxygen or any other oxidizing atmosphere, the oxidation treatment temperature is 250-650° C., preferably 300-600° C., and the treatment time is 1-8 hours.
[0025] In some embodiments of the present invention, the solid copper powder B is atomized copper powder having a spherical or quasi-spherical shape.
[0026] In some embodiments of the present invention, in step 2) and step 2.2), the cooling comprises cooling to below 40°C;
[0027] The crushing is carried out by adding an antioxidant in a crusher, and the frequency of the crusher is 30 to 60 Hz;
[0028] The antioxidant is at least one of dibutylphenol, sodium thiosulfate and sodium sulfite.
[0029] In a second aspect, the present invention discloses a method for preparing the composite copper powder according to the first aspect, the method comprising compositely mixing porous copper powder A and solid copper powder B.
[0030] In a third aspect, the present invention discloses a heat sink, which is manufactured by molding and sintering the composite copper powder described in the first aspect using a heat sink mold.
[0031] The beneficial effects of the technical solution disclosed in the present invention are mainly reflected in the following:
[0032] The present invention provides a composite powder having a "capillary-permeability dual channel" with controllable pore size and controllable bulk ratio formed by compounding a porous copper powder A with a special microscopic morphology with a solid copper powder B. The composite powder is used to prepare a heat pipe, and the capillary force and the permeability of the heat pipe can achieve an excellent match. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0034] Figure 1 The microscopic morphology of the composite copper powder in Example 2 according to the embodiment of the present invention is schematically shown;
[0035] Figure 2 The microscopic morphology diagram of the composite copper powder in Example 3 according to the embodiment of the present invention is schematically shown. DETAILED DESCRIPTION
[0036] In the prior art, copper powder and copper tubes are filled and vibrated and sintered to prepare heat pipes. This composite structure of copper powder and copper tube requires that the copper powder used must be more irregular to ensure that the capillary structure holes are more refined after sintering and show stronger capillary force. On the other hand, the shrinkage rate of the copper powder needs to be controlled to ensure that the copper powder and the inner wall of the copper tube have good bonding strength. Therefore, how to provide a copper powder that has a simple preparation process and can be used for mass production of copper heat pipes with excellent performance is a technical problem that needs to be solved at present.
[0037] In order to solve the above technical problems, the present invention provides a composite copper powder and a preparation method and application thereof. A composite powder with a controllable pore size and a controllable bulk ratio and a "capillary-permeability dual channel" is formed by compounding a porous copper powder A with a special microscopic morphology with a solid copper powder B. The composite powder is used to prepare a heat pipe, and the capillary force and permeability of the heat pipe can achieve an excellent match.
[0038] At the same time, the "loose ratio" in the present invention is also called "loose density", and its measurement method is a commonly used method in the field.
[0039] The first aspect of the present invention to achieve the above technical effects is to provide a composite copper powder, the copper powder is composed of a porous copper powder A and a solid copper powder B, the porous copper powder A is a spherical or quasi-spherical powder, the spherical or quasi-spherical powder contains interconnected cuprous powders, the cuprous powders are dendritic, and each dendritic cuprous powder is cross-stacked to form the porous structure; the pore size of each pore of the porous structure is 0.1 to 5 μm, and the porosity is 10 to 75%; and the bulk ratio of the composite copper powder is 0.8 to 2.8 g / cm 3 .
[0040] The particle size of the "cuprous powder" is smaller than that of the spherical or quasi-spherical powder. It is a particle that describes the microscopic morphology of copper powder. The specific morphology and specific particle size are not limited in the present invention.
[0041] Exemplarily, the porosity is any one of 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75% or any one satisfying the above range.
[0042] Exemplarily, the bulk ratio of the composite copper powder is 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 Any one of or any one satisfying the above range.
[0043] In some embodiments, the bulk ratio of the porous copper powder A is 0.8 to 2.4 g / cm 3 , preferably 0.8 to 1.0 g / cm 3 The particle size of the porous copper powder A is -60 to +200 mesh, where 60 mesh corresponds to 250 μm, 200 mesh corresponds to 75 μm, and 50% ≤ -60 to +150 mesh ≤ 55 to 70%. The "+" in front of the mesh number represents sifting, and the "-" represents not sifting.
[0044] For example, the bulk ratio of the porous copper powder A is 0.8 g / cm 3 , 0.9g / cm 3, 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 Any one of or any one satisfying the above range.
[0045] In some embodiments, the bulk ratio of the solid copper powder B is 2.2 to 3.8 g / cm 3 , preferably 2.4 to 2.8 g / cm 3 The particle size of the solid copper powder B is D50=50-150 μm, preferably D50=50-80 μm.
[0046] For example, the bulk ratio of the solid copper powder B is 2.2 g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 、3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 Any one of or any one satisfying the above range.
[0047] In some embodiments, the solid copper powder B is atomized copper powder having a spherical or quasi-spherical shape.
[0048] In some embodiments, the solid copper powder B is prepared by water atomization, and atomization parameters are controlled to obtain atomized copper powder with a suitable bulk ratio.
[0049] In some embodiments, the mass ratio of the porous copper powder A to the solid copper powder B is (1-9):(9-1).
[0050] Exemplarily, the mass ratio of the porous copper powder A to the solid copper powder B is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 2:1, 2:2, 2:3, 2:4, 2:5, 2:6, 2:7, 2:8, 2:9, 5:1, 5:2, 5:3, 5:4, 5:6, 5:7, 5:8, 5:9, 7:1, 7:2, 7:3, 7:4, 7:5, 7:6, 7:7, 7:8, 7:9, 9:1, 9:2, 9:3, 9:4, 9:5, 9:6, 9:7, 9:8, or any one of the above ranges.
[0051] In some embodiments, the porous copper powder A is prepared by subjecting a copper oxide powder raw material to thermal reduction treatment; the copper oxide powder raw material is a copper oxide powder having a porous structure and / or a hollow structure;
[0052] The copper oxide powder with a porous structure is at least one of electroplating grade copper oxide and calcined grade copper oxide; the particle size of the copper oxide powder with a porous structure satisfies: D50=28-40 μm;
[0053] The copper oxide powder having a hollow structure is a powder having a particle size of 1.0 to 100 μm obtained by reduction-oxidation treatment of cuprous oxide.
[0054] Wherein, the electroplating grade copper oxide and the calcined grade copper oxide can both be commercial varieties, which will not be elaborated in the present invention.
[0055] The specific preparation process of the copper oxide powder with a hollow structure is as follows:
[0056] Cuprous oxide is selected for screening / mixing / ball milling, and then solid phase reduction oxidation heat treatment is carried out, and the oxidation-reduction product is cooled, crushed, granulated and sieved to obtain a hollow structured copper oxide powder.
[0057] The copper oxide powder with a hollow structure obtained by the preparation method is a hollow microsphere with a multi-microporous structure on the surface and a large hole inside. The particle size of the hollow microsphere is 1.0-100 μm, the shell thickness of the hollow microsphere is 0.2-2.0 μm, and the hollow diameter is 1.0-5.0 μm.
[0058] In some embodiments, when the copper oxide powder raw material is composed of copper oxide powder with a porous structure and copper oxide powder with a hollow structure, the mass ratio of the two is (1-9):(9-1).
[0059] Exemplarily, the mass ratio of the two is 1:9, 5:5, 9:1, or any one within the above range.
[0060] In some embodiments, the bulk ratio of the copper oxide powder raw material is 0.6 to 1.5 g / cm 3 , preferably 0.8 to 1.2 g / cm 3 The copper content in the copper oxide powder raw material is ≥97% by mass.
[0061] For example, the bulk ratio of the copper oxide powder raw material is 0.6 g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 Any one of or any one satisfying the above range.
[0062] The preparation method of the porous copper powder A comprises the following steps:
[0063] 1) subjecting a copper oxide powder raw material to a thermal reduction treatment to obtain a reduction pre-treated product;
[0064] 2) Cooling, crushing and sieving the reduction pre-treated product of step 1) to obtain the porous copper powder A.
[0065] In some embodiments, the method further comprises subjecting the reduction pre-treated product obtained in step 1) to the following treatment:
[0066] 2.1) the reduction pretreatment product is subjected to oxidation treatment to obtain an oxidation product;
[0067] 2.2) the oxidation product is further subjected to thermal reduction treatment;
[0068] The step 2.1) and the step (2.2) are repeated 1 to 6 times, and then cooled, crushed, and sieved to obtain the porous copper powder A. The oxidation treatment further expands the volume of the pore wall on the basis of the original preliminary porosity, which is conducive to the formation of secondary micropores with more developed morphology. The oxidation-reduction treatment can be repeated multiple times to achieve multiple pore formations, and finally obtain a porous copper powder with diversified micropore structures, adjustable pore size range, and multi-level pore structure.
[0069] In some embodiments, the thermal reduction treatment in step 1) and step 2.2) is carried out in a reducing atmosphere containing nitrogen, the volume percentage of nitrogen in the reducing atmosphere is 10 to 90%, preferably ammonia decomposition gas; wherein the reducing atmosphere also contains at least one of hydrogen, carbon monoxide, and hydrogen sulfide.
[0070] The temperature of the thermal reduction treatment is 300-900° C., preferably 400-800° C., and the treatment time is 1-8 hours.
[0071] Exemplarily, the thermal reduction temperature is any one of 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C or any one satisfying the above range.
[0072] Exemplarily, the processing time is any one of 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h or any one satisfying the above range.
[0073] Exemplarily, the thermal reduction can be performed in a pusher furnace, a mesh belt furnace, a rotary kiln or an atmosphere protection furnace.
[0074] In some embodiments, the oxidation treatment in step 2.1) is carried out in air, high-purity oxygen or any other oxidizing atmosphere, the oxidation treatment temperature is 250-650° C., preferably 300-600° C., and the treatment time is 1-8 hours.
[0075] Exemplarily, the oxidation temperature is any one of 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or any one satisfying the above range.
[0076] Exemplarily, the processing time is any one of 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h or any one satisfying the above range.
[0077] Exemplarily, the oxidation can be performed in a muffle furnace, a tube furnace, an atmosphere furnace, a roller kiln or a rotary kiln.
[0078] In some embodiments, the crushing is performed in a crusher, the frequency of the crusher is 30-60 Hz, and the sieve used for the screening is 60-200 mesh, such as 60→100→150→200 mesh sieves in sequence.
[0079] The antioxidant is at least one of dibutylphenol, sodium thiosulfate and sodium sulfite. The crushing and granulation method can be any one of roller crushing, jaw crushing, air flow crushing and ball mill crushing.
[0080] The second aspect of the present invention to achieve the above technical effect is to provide a method for preparing the compound copper powder described in the first aspect, the method comprising compounding and mixing porous copper powder A and solid copper powder B. The mixing here can be any mixing method.
[0081] The third aspect of the present invention to achieve the above technical effects is to provide a heat sink, which is made by injecting the compound copper powder described in the first aspect or the compound copper powder obtained by the method described in the second aspect into a heat sink mold and sintering it.
[0082] Example 1 to Example 10
[0083] Provided is a composite copper powder, wherein the preparation process and performance parameters of porous copper powder A are shown in Table 1, and the composition and performance parameters of the composite copper powder are shown in Table 2.
[0084] Table 1 Preparation process and performance parameter list of porous copper powder A
[0085]
[0086]
[0087]
[0088] Among them, the particle size of the porous copper powder A in Table 1 is -60 to +200 mesh.
[0089] Table 2 Composition and performance parameters of compound copper powder
[0090]
[0091] in, Figure 1 and Figure 2 The microscopic morphology of the composite copper powder prepared in the example.
[0092] The copper powder obtained in the above embodiments 1 to 10 is used to make a heat pipe, and is tested according to the technical requirements of the heat pipe copper powder. The specific test method is: the sample is placed in a graphite mold and vibrated at a frequency of 50 Hz for 1 min, and then the graphite mold and the powder are placed in a sintering furnace, and sintered at a constant temperature of 950° C. in a hydrogen protective atmosphere for 1.5 hours, and then cooled to 40-60° C. with the furnace, and the graphite mold is taken out, and the powder sintering sample is taken out.
[0093] Among them, the properties of the copper powder after sintering are as shown in Table 3;
[0094] Table 3 Properties of copper powder prepared in Examples 1 to 10 after sintering
[0095]
[0096]
[0097] Among them, the standard used to calculate the porosity in Table 1 is GB / T 5163-2006, and the radial shrinkage test method is set and measured according to the industry standard YS / t 1337-2019 heat pipe copper powder mold. The maximum pore size test procedure is based on GB / T 5249-2013, and the permeability test procedure is based on GB / T 5250-2014. The porosity, radial shrinkage, and maximum pore size in the embodiment are combined to determine the capillary force of the sample. The smaller the maximum pore size, the stronger the capillary force. At the same time, there is also a very good test result for the osmotic pressure. Therefore, the composite powder is used to prepare heat pipes, and the capillary force and permeability of the heat pipes can achieve excellent matching.
[0098] It should be understood that the terms used herein are only for the purpose of describing specific example embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "an" and "said" as used herein may also be meant to include plural forms. The terms "include", "comprise", "contain", and "have" are inclusive, and therefore specify the existence of stated features, steps, operations, elements and / or parts, but do not exclude the existence or addition of one or more other features, steps, operations, elements, parts, and / or combinations thereof. The method steps, processes, and operations described herein are not interpreted as necessarily requiring them to be performed in the specific order described or illustrated, unless the execution order is clearly indicated. It should also be understood that additional or alternative steps may be used.
[0099] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A composite copper powder, characterized in that: The composite copper powder is composed of porous copper powder A and solid copper powder B, wherein the porous copper powder A is spherical or quasi-spherical powder, the spherical or quasi-spherical powder contains interconnected cuprous powder, the cuprous powder is dendritic, and each dendritic cuprous powder is cross-stacked to form a porous structure; the pore size of each pore of the porous structure is 0.1-5 μm, and the porosity is 10-75%; and the bulk ratio of the composite copper powder is 0.8-2.8 g / cm 3 ; The porous copper powder A is prepared by subjecting a copper oxide powder raw material to a thermal reduction treatment to obtain a reduction pretreatment product, the reduction pretreatment product to an oxidation product by oxidation treatment, and the oxidation product to a thermal reduction treatment to obtain the porous copper powder A; The temperature of the oxidation treatment is 250-650°C; The particle size of the porous copper powder A is -60 to +200 mesh; The particle size D50 of the solid copper powder B is 50-150 μm.
2. The composite copper powder according to claim 1, characterized in that The bulk ratio of the porous copper powder A is 0.8-2.4 g / cm 3 .
3. The composite copper powder according to claim 1, characterized in that: The bulk ratio of the porous copper powder A is 0.8-1.0 g / cm 3 .
4. The composite copper powder according to claim 1, characterized in that The particle size of the porous copper powder A satisfies: 50%≤-60~+150 mesh≤55~70%.
5. The composite copper powder according to claim 1, characterized in that: The bulk ratio of the solid copper powder B is 2.2 to 3.8 g / cm 3 .
6. The composite copper powder according to claim 1, characterized in that: The bulk ratio of the solid copper powder B is 2.4-2.8 g / cm 3 ; and / or; The particle size D50 of the solid copper powder B is 50-80 μm.
7. The composite copper powder according to claim 1, characterized in that: The mass ratio of the porous copper powder A to the solid copper powder B is (1-9):(9-1).
8. The composite copper powder according to any one of claims 1 to 7, characterized in that: The porous copper powder A is prepared by subjecting a copper oxide powder raw material to a thermal reduction treatment; the copper oxide powder raw material is a copper oxide powder having a porous structure and / or a hollow structure; The copper oxide powder with a porous structure is at least one of electroplating grade copper oxide and calcined grade copper oxide; the particle size of the copper oxide powder with a porous structure satisfies: D50=28-40 μm; The copper oxide powder having a hollow structure is a powder having a particle size of 1.0 to 100 μm obtained by reduction-oxidation treatment of cuprous oxide.
9. The composite copper powder according to claim 8, characterized in that: The bulk ratio of the copper oxide powder raw material is 0.6-1.5 g / cm 3 .
10. The composite copper powder according to claim 8, characterized in that: The bulk ratio of the copper oxide powder raw material is 0.8-1.2 g / cm 3 .
11. The composite copper powder according to claim 8, characterized in that: When the copper oxide powder raw material is composed of copper oxide powder with a porous structure and copper oxide powder with a hollow structure, the mass ratio of the two is (1-9):(9-1).
12. The composite copper powder according to claim 8, characterized in that: The porous copper powder A is prepared by subjecting a copper oxide powder raw material to a thermal reduction treatment, comprising the following steps: 1) subjecting a copper oxide powder raw material to a thermal reduction treatment to obtain a reduction pre-treated product; 2) Cooling, crushing and sieving the reduction pre-treated product of step 1) to obtain the porous copper powder A.
13. The composite copper powder according to claim 12, characterized in that: The porous copper powder A is prepared by the following treatment method: 1) subjecting a copper oxide powder raw material to a thermal reduction treatment to obtain a reduction pre-treated product; 2.1) the reduction pretreatment product is subjected to oxidation treatment to obtain an oxidation product; 2.2) the oxidation product is further subjected to thermal reduction treatment; The steps 2.1) and (2.2) are repeated 1 to 6 times, and then cooled, crushed and sieved to obtain the porous copper powder A.
14. The composite copper powder according to claim 13, characterized in that: The thermal reduction treatment in step 1) and step 2.2) is carried out in a reducing atmosphere containing nitrogen, wherein the volume percentage of nitrogen in the reducing atmosphere is 10 to 90%; The temperature of the thermal reduction treatment is 300-900°C; The oxidation treatment in step 2.1) is carried out in air, high-purity oxygen or any other oxidizing atmosphere, and the temperature of the oxidation treatment is 250-650°C.
15. The composite copper powder according to claim 14, characterized in that: The reducing atmosphere is ammonia decomposition gas.
16. The composite copper powder according to claim 14, characterized in that: The temperature of the thermal reduction treatment is 400-800° C., and the treatment time is 1-8 hours.
17. The composite copper powder according to claim 14, characterized in that: The temperature of the oxidation treatment is 300-600° C., and the treatment time is 1-8 hours.
18. The composite copper powder according to any one of claims 1 to 7, characterized in that: The solid copper powder B is atomized copper powder having a spherical or quasi-spherical shape.
19. A heat sink, characterized in that: The heat sink is made by molding and sintering the composite copper powder according to any one of claims 1 to 18 using a heat sink mold.
